Virulence-Inhibiting Herbal Compound Falcarindiol Significantly Reduced Mortality in Mice Infected with Pseudomonas aeruginosa - Pansong Zhang; Qiaolian Wu; Lin Chen; Kangmin Duan (MDPI AG, 2020)
Antipathogenic compounds that target the virulence of pathogenic bacteria rather than their viability offer a promising alternative approach to treat infectious diseases. Using extracts from 30 Chinese herbs that are known for treating symptoms resembling infections, we identified an active compound falcarindiol from Notopterygium incisum Ting ex H. T. Chang that showed potent inhibitory activities against Pseudomonas aeruginosa multiple virulence factors. Falcarindiol significantly repressed virulence-related genes, including the type III secretion system (T3SS); quorum sensing synthase genes lasIR and rhlIR; lasB; motility-related genes fliC and fliG; and phenazine synthesis genes phzA1 and phzA2. P. aeruginosa swarming motility and pyocyanin production were reduced significantly. In a burned mouse model, falcarindiol treatment significantly reduced the mortality in mice infected with P. aeruginosa, indicating that falcarindiol is a promising antipathogenic drug candidate for treating P. aeruginosa infections.